'Overjoyed that I can go outside': Using walking interviews to learn about the lived experience and meaning of neighbourhood for people living with dementia. (October 2020) - Odzakovic, Elzana; Hellström, Ingrid; Ward, Richard; Kullberg, Agneta
This study explores the relationships between people living with dementia and their neighbourhood as they venture out from home on a regular and often routine basis. Here, we report findings from the Swedish field site of an international 5-year project: Neighbourhoods: our people, our places. The aims of this study were to investigate the lived experience of the neighbourhood for people with dementia and through this to better understand the meaning that neighbourhood held for the participants. In this study, we focus on the walking interviews which were conducted with 14 community-dwelling people with dementia (11 men and 3 women) and were analysed using an interpretative phenomenological method. Four themes were revealed from these interviews: life narratives embedded within neighbourhood; the support of selfhood and wellbeing through movement; the neighbourhood as an immediate social context; and restorative connections to nature. These themes were distilled into the 'essence' of what neighbourhood meant for the people we interviewed: A walkable area of subjective significance and social opportunity in which to move freely and feel rejuvenated. We have found that the neighbourhood for community-dwelling people with dementia holds a sense of attachment and offers the potential for freedom of movement. Our research indicates that a dementia diagnosis doesn't necessarily reduce this freedom of movement. The implications for practice and policy are considered: future research should explore and pay closer attention to the diverse living conditions of people living with dementia, and not least the particular challenges faced by people living alone with dementia.